Diatoms in wetlands from the south-west of Western Australia: community structure in relation to pH - Thomas, E.; John, Jacob (Royal Society of Western Australia, 2010)
A total of 20 wetlands representing three distinct pH groups from the south-west of Western Australia were sampled over three seasons to investigate the relationship between pH and diatom community structure. Multi-dimensional scaling and analyses of similarities were used to identify differences in the diatom community structure according to geographical locations and pH groupings. Regional differences in diatom assemblages were largest between the Collie and Wagerup sites and were associated with varying pH. The largest differences among pH groups were evident between the acidic Group 1 and alkaline Group 3 sites; differences in comparisons were less defined with the circumneutral Group 2 wetlands. BIO-ENV analyses showed that pH was the variable most strongly correlated with diatom distribution patterns during each season. Potential indicator species were identified for each pH group, including Brachysira brebissonii, Frustulia magaliesmontana, Nitzschia paleaeformis, Brachysira vitrea and Staurosira construens var. venter. The results also indicated that diatoms were useful biological indicators of pH in various seasons and can therefore be incorporated into monitoring programs for pH changes in the wetlands of the south-west of Western Australia.